Value of roentgenologic examination in diagnostics of pneumoconiosis associated with chronic obstructive pulmonary disease in workers of the mining and metallurgical industry. - R. V. Rubtsov (Medičnì Perspektivi)
The aim of the research is to study the peculiarities of changes in the chest on survey radiograph at pneumoconiosis associated with COPD in workers of mine and metallurgical industry.  The data of clinical examination of 635 workers with lung pathology of occupational genesis are presented in the article. Group I consisted of 99 workers with pneumoconiosis associated with COPD, II group – of 21 workers with pneumoconiosis, and III group – of 515 workers with COPD of occupational etiology. A comparative analysis of radiographic changes in the chest X-ray has established that the most informative radiologic changes for pneumoconiosis associated with COPD are: linear reticular obscuration up to 1.5 mm in size, cord obscuration from 1.5 to 3.0 mm in size, and less significant changes in the form of nodules size up to 1.5 mm, from 1.5 to 3.0 mm, the thickening of pleura more than10.0 mmwide. The most sensitive radiographic signs typical for PC associated with COPD are the indicated obscurations and nodules, their etiological share in diagnosis of this disease is 100%, determining the greatest absolute risk of development of this occupational pathology in this category of patients. The revealed X-ray diagnostic criteria allow to conduct timely diagnostics, define the tactics of treatment and prevention of PC associated with COPD in workers of mining and metallurgical industry.